Case report on the role of aggressive palliative surgery in lung NUT carcinoma after induction chemoimmunotherapy. (April 2023) - Alcasid, Nathan J.; Banks, Kian C.; Sun, Angela; Velotta, Jeffrey B.
Abstract: Introduction and importance: NUT (nuclear protein in testis) carcinoma of the lung is an aggressive, poorly differentiated squamous cell carcinoma that has a poor prognosis. Currently, there are no recommended guidelines with limited literature regarding the management of primary NUT carcinoma of the lung. Case presentation: A 28-year-old male presented with 2 weeks of intractable chest pain and shortness of breath and was found to have Stage IV pleural NUT carcinoma. After 2 cycles of chemoimmunotherapy, the patient's symptoms persisted with worsening functional status. Palliative surgery was performed via an extrapleural pneumonectomy with significant improvement in symptoms and activities of daily living. Clinical discussion: With no current treatment guidelines, we demonstrate the benefit of surgical resection of advanced pleural NUT carcinoma to improve quality of life. Prognosis is poor with a median survival around 7 months and 3 months with an associated mass. The patient presented pre-operatively with intractable pleuritic chest pain and shortness of breath, limiting activities of daily living that persisted despite chemoimmunotherapy. Our surgical goal was to improve the patient's respiratory status and mitigate pain symptoms via extensive surgical debulking. The patient was able to achieve a higher quality of life and survived longer than the median average, passing away 1 year after diagnosis. Conclusion: The management of NUT carcinoma of the lung remains challenging. The role of surgical resection for palliation in advanced tumors has not been previously described and may provide improved quality of life in carefully selected patients. Highlights: NUT carcinoma is a subset of squamous cell cancers that is rare and aggressive. There are no current treatment guidelines for metastatic NUT carcinoma of the lung. Palliative surgical debulking may be an option to improve quality of life.